Penerapan Arsitektur Islam Modern pada Desain Muallaf Center di Kota Makassar - Wahyudi, Didi; Marwati, Marwati; A'raaf Tauhid, Fahmyddin (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2022)
The development of converts in eastern Indonesia, especially in Makassar, is fast but not followed by structured facilities and guidance. The center's design for the development and empowerment of converts to Islam in the city of Makassar needs to be using a modern Islamic architectural approach. Modern Islamic architecture is a collaboration between Islamic architecture and modern architecture. The concept of modern Islamic architecture is an architectural approach that applies Islamic values ​​to the design of buildings with easily recognizable characteristics such as ornaments and simple openings. Qualitative descriptive and design exploration methods are used for designing and applying ornament applications to buildings. The purpose of writing is to apply modern Islamic architectural ornaments on the facade of the building. The design results found that the application for the design according to the function. The converts are more applied to the front in the form of ornaments and windows.